A study of the self-reversal process of rhyodacites from Haruna volcano, Japan and those from the 1991 Pinatubo eruption, Philippines - ORLICKÝ, Oto (Contributions to Geophysics and Geodesy, 2011)
The results of the study of young rhyodacites (erupted in 1400 year) from theHaruna area (Japan) and from the 1991 Pinatubo eruption (Philippines) are presented.The experimental works have proven that the Fe-Ti ferrimagnetic-antiferromagnetic phaseis the carrier of the self-reversed remanent magnetization in these rocks. The theoreticalsolution of this problem has been outlined, but has not yet been accomplished